Volatile compounds in dry dog foods and their influence on sensory aromatic profile - Koppel, Kadri; Adhikari, Koushik; Di Donfrancesco, Brizio (My University, 2013)
The aim of this study was to determine volatile compounds in dry dog foods and their possible influence on sensory aromatic profile. Grain-free dry dog foods were compared to dry dog foods manufactured with grain, but also with different protein sources for their aromatic volatiles. Solid-phase microextraction/gas chromatography/mass spectrometry was used to determine the aromatic compounds present in the headspace of these samples. Partial Least Squares regression was performed to correlate the instrumental aromatic data with the descriptive aroma analysis data. A total of 54 aromatic compounds were tentatively identified in the dry dog food samples, with aldehydes and ketones being the most represented organic volatiles group. Grain-added products were on the average higher in total volatiles than grain-free products. Partial Least Squares regression analysis indicated possible connections with sensory aromatic profile and grain-added samples, such as rancid aroma and aldehydes, especially hexanal. The results of this study showed that dry dog foods are products with complex odor characteristics and that grain-free products are less aromatic.
Keywords: Descriptive sensory analysis; Headspace-solid phase microextraction; Dog food; Volatile compounds